Evaluating judgments and decisions related to lawsuits involving aesthetic plastic surgery - Fabio Hideki Júlio Oshiro (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: There is a legal consensus that the results of medical activities represent obligations of means, not results. However, there is ample discussion when it comes to aesthetic procedures. Resolution 1621/2001 of the Federal Council of Medicine also defines the objective of a medical act in plastic surgery as an obligation of means. This study evaluated 106 cases between November 2015 and November 2017 to verify whether the decisions of the Judicial Power agree with the Resolution of the Federal Council of Medicine. The number of lawsuits and the percentage of claims granted or denied were quantified, and the opinions of jurists and courts that supported the claims granted were verified. The number of cases in which the judge's decision was related to the opinion of a medical expert was also quantified. Methods: The authors searched the judgment database located on the website of the Court of Justice of the State of São Paulo (SP) for damage related to aesthetic plastic surgery, using the keyword "Plastic Surgery" for all actions. Results: A total of 61 claims (58%) were denied, and 45 (42%) were granted. In 96% of cases (102) the judgment was positively related to the expert report. Conclusion: There were 102 cases in which the judgment agreed with the expert reports and only four cases in which the judgment did not agree with the reports. These data show the crucial importance of experts' reports in defining judicial judgments. The analyses of all judgments showed that there were no cases in which the judge considered the Resolution of the Federal Council of Medicine.